PEMBERDAYAAN PENYANDANG DISABILITAS DI KOTA PEKANBARU MELALUI DINAS SOSIAL KOTA PEKANBARU TAHUN 2019 - Yudi Kurniawan; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Persons with disabilities constitutionally have the same rights and positions as other citizens before the law and government. So that the empowerment of persons with disabilities aims to develop the potential that exists within persons with disabilities so that they are able to work even though they have some limitations. The writing of this thesis is motivated by the researcher's view of the phenomenon that occurs the lack of participation of persons with disabilities in sewing training held by the Pekanbaru City government so that several problems emerged that were found by the authors related to the empowerment of the potential of persons with disabilities in the city of Pekanbaru. The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Pekanbaru City. With the type and source of research data, it is divided into primary data in the form of purposive informant collection techniques and secondary data in the form of supporting data related to persons with disabilities. Data collection techniques using interviews, documentation and document tracing. while data analysis was carried out using qualitative analysis. The results of this study are firstly that the empowerment of people with disabilities by the Pekanbaru City Social Service has not run optimally so that people with disabilities are not empowered, it can be seen from (1) human development is carried out by training and socialization but many people with disabilities do not participate, (2) business development is carried out with a bazaar and facilities for persons with disabilities to develop their businesses, (3) community development is realized with motivation from the immediate family environment (4) institutional development is the role of workshop development institutions to provide a forum for channeling talents possessed by people with disabilities. The two factors that support the empowerment of disability by the Pekanbaru City Office are (a) central and local government support (b) environmental support (c) organizational support (d) facilities and infrastructure. While the inhibiting factor is the lack of government role and support from the general public Keywords: Empowerment, Disability, Social Service